Edukasi dan Aksi Kemanusiaan: Kegiatan Donor Darah di Balai Desa Sei Gelugur, Kecamatan Pancur Batu, Kabupaten Deli Serdang - Nela Rosa; Martina Evlyn Romauli Hutahaean; Maita Sarah; Harry Permana Wibowo; Elyani Sembiring; Dameria Br Ginting; Arlis Arlis; Kalvin Ginting; Marthalena Siahaan; Mazly Astuty (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
This community service project was conducted through a blood donation campaign at the Sei Gelugur Village Hall, Pancur Batu District, Deli Serdang Regency. The activity aimed to foster a healthy lifestyle and increase community awareness about the importance of blood donation as a humanitarian act. This event was a collaboration between the Indonesian Red Cross (PMI) Medan City and the Institute of Health of North Sumatra, involving nursing students in the community nursing stage. The activity was carried out on July 4, 2025, from 09.00–12.00 WIB, providing education and conducting a blood donation drive for the community, and it received strong enthusiasm from the community. The results showed increased awareness, participation, and understanding among residents regarding the importance of regular blood donation, which supports national blood supply sustainability and strengthens social solidarity.